Deteksi Keberadaan Parasit Anisakis sp. Pada Ikan Layang (Decapterus sp.) Yang Diperdagangkan Di Pasar Ikan Kedonganan, Bali - Siti Komariah; I Gde Suranaya Pandit; Ni Made Darmadi (Fakultas Pertanian, Universitas Warmadewa, 2020)
This study aims to determine the presence of Anisakis sp. and the prevalence of infection in ikan layang (Decapterus sp.) traded at the Kedonganan Fish Market, Badung Regency, Bali for three days. The study was conducted in March-April 2020 at the Food Analysis Laboratory of the Faculty of Agriculture, Warmadewa University, Denpasar. The method used in this research is descriptive which is a method for describing the presence of Anisakis sp. in ikan layang traded in Traditional and Hygienic Markets in Kedonganan, Badung Regency, Bali. Tests in this study include examination of parasites in the digestive tract of ikan layang, identification of parasites Anisakis sp. and prevalence. Assessment of raw material for ikan layang as an organoleptic sample and identification of ikan layang was also taken as supporting data in this study. The results showed that the raw material for ikan layang samples on the first day of sampling was still in good condition and had the same characteristics or ikan layang as the species of Decapterus ruselli. While the results of the detection of the presence of parasites Anisakis sp. in ikan layang showed that from 30 samples of ikan layang, there were 25 samples that were positively infected by stage three larvae of Anisakis sp. resulting in a prevalence of 83.33% (Usually). The parasite was found attached to the abdominal cavity, the surface of the outer wall of the stomach, intestines and fish flesh.